2017
DOI: 10.1016/j.expthermflusci.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of dynamic concentration of nanofluid in laminar flow

Abstract: Nanofluid is thought to have a potential enhancement in heat transfer behaviour of fluid. The nanoparticle concentration in nanofluid is one of the most important factors that affect the nanofluid behaviour. The static concentration was applied in the researches under flowing condition. In this paper, Nuclear Magnetic Resonance (NMR) scanning was applied to study the dynamic concentration of nanofluid flow in pipe. The experiments were carried out with ferrofluid under different concentration and temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Hong et al [12] investigated the dynamic concentration of nanofluids in laminar low and proposed an empirical equation to calculate the concentration of nanoparticles in a pipe. It was found that the concentration of nanofluids decreases from the wall to centre in the pipe and it has a maximum value near the pipe wall.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [12] investigated the dynamic concentration of nanofluids in laminar low and proposed an empirical equation to calculate the concentration of nanoparticles in a pipe. It was found that the concentration of nanofluids decreases from the wall to centre in the pipe and it has a maximum value near the pipe wall.…”
Section: Introductionmentioning
confidence: 99%